Updating Numerical Models of Masonry Arch Bridges by Operational Modal Analysis - Cristina Costa (2015)
This article aims at presenting and discussing the strategies for updating the finite element numerical modeling of stone masonry arch bridges using operational modal analysis. The study comprehended three bridges: two old ones, the St. Lazaro and the Lagoncinha bridges, and a recently constructed bridge in Vila Fria, Portugal. Updating of the bridge models is performed by comparing the numerical and experimental modal parameters. Three-dimensional detailed numerical models are used to perform modal analysis of the bridges. Experimental modal identification of the bridges is based on the measurement of their acceleration responses during normal operation. The assigned material properties are also based on available results obtained from in situ and laboratory tests and on the results of visual inspection and historical research carried out for both old bridges.